EFEKTIFITAS PEMAKAIAN BLANKET WARMER TERHADAP PASIEN MENGGIGIL PASCA ANESTESI REGIONAL DI RUANG PEMULIHAN DI RSUD KOTA TANGERANG - Usep Hidayatulloh (Jurnal Inovasi Penelitian, 2023)
Regional anesthesia is a more analgesic anesthesia technique due to the pain that disappears in the blocked regional part (A. Pramono, 2019). Surgery can cause physiological changes in the body, namely a decrease in body temperature / hypothermia. A non-pharmacological approach to keep the body from hypothermia is carried out by warming methods including the use of blanket warmers, oxygen humidification, and intravenous fluid heating. This type of research uses the Causal type of design using quantitative design and uses the Pre experimental one group pre and post test design method, namely this study is intended to test the influence of independent variables on dependent variables where one group is observed temperature before and after the desired intervention (Nursalam, 2017). Based on the output of "Test Statistics" above, it is known to Asymp.Sig. (2-tailed) is worth 0.000. Since the value of 0.000 is less than 0.05, it can be concluded that "Ha is accepted". This means that there is a difference between the Initial Temperature and the Temperature After Blanket Warmer Administration After 50 Minutes, so it can also be concluded that "there is an effect of giving blanket warmer after 50 minutes on the patient". it can be concluded that "Ha is accepted". This means that there is a difference between the Initial Temperature and the Temperature After Blanket Warmer Administration After 50 Minutes, so it can also be concluded that "there is an effect of giving blanket warmer after 50 minutes on the patient".